2022
DOI: 10.18844/cjes.v17i4.7145
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles of teaching distance universities courses in light of E-learning quality standards

Abstract: The current study aimed to identify the obstacles of teaching courses during distance learning in light of e-learning quality standards. A survey consisting of 21 items was gathered from 146 faculty staff members during the first semester of the academic year (2021–2022). To achieve the objectives of this study, a questionnaire was used after verifying its psychometric properties. The results of the study revealed a moderate level of obstacles to teaching courses in distance education. Moreover, the study find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Ozudogr (2021) conducted a study aimed at investigating the problems faced by preservice teachers in the distance education process, which has been implemented during the COVID-19 pandemic. The researcher used interviews to collect data (Alnasraween, et al, 2022), The study sample consisted of 241 pre-service teachers and technical The study results showed that the pre-service teachers mainly faced problems such as the lack of time spared for live courses regarding "implementation", failure to establish communication with friends regarding "student", absence of internet regarding "impossibility", sound problems regarding "technical" and lack of communication regarding "instructor". H2: System quality has a significant and positive effect on e-learning adoption.…”
Section: System Qualitymentioning
confidence: 99%
“…Ozudogr (2021) conducted a study aimed at investigating the problems faced by preservice teachers in the distance education process, which has been implemented during the COVID-19 pandemic. The researcher used interviews to collect data (Alnasraween, et al, 2022), The study sample consisted of 241 pre-service teachers and technical The study results showed that the pre-service teachers mainly faced problems such as the lack of time spared for live courses regarding "implementation", failure to establish communication with friends regarding "student", absence of internet regarding "impossibility", sound problems regarding "technical" and lack of communication regarding "instructor". H2: System quality has a significant and positive effect on e-learning adoption.…”
Section: System Qualitymentioning
confidence: 99%
“…Several countries face many obstacles and gaps in the distance learning process (Illarionova et al, 2021;Salman & Shahadab, 2022;Svobodova et al, 2021). However, to ensure students can still study even in the midst of the Covid-19 pandemic, distance learning still needs to be done.…”
Section: Introductionmentioning
confidence: 99%
“…Educational e-learning is one of the factors that enhance learning and therefore is always emphasized. Educational e-learning means integrating e-learning in such a way that leads enhancement of learning process (Alnasraween & Shahadab, 2022). It is a practice by which the learning and teaching process can be improved (pandey, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In some educational systems, e-learning integration has been regarded among the top priorities in policy making, budget planning, and curriculum development. At the same time, e-learning is recognized as one of the key drivers for the improvement of teaching and learning (Alnasraween & Shahadab, 2022;Afshari, Bakar, Wong, Samah & Fooi, 2008;Wong, Atan & Sabudin, 2010), prompting governments to launch major initiatives and make considerable capital investments to build and maintain information communication e-learning (ICT) infrastructures in the schools (Moses, Khambari & Wong, 2008). In recent years, the Internet has not only fostered rapid access to information; it also facilitated changes in the nature of today's education (Pham & Tran, 2020).…”
Section: Introductionmentioning
confidence: 99%